1998
DOI: 10.1074/jbc.273.44.28553
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of cDNA Encoding a Novel Mouse DNA Topoisomerase III (Topo IIIβ) Possessing Negatively Supercoiled DNA Relaxing Activity, Whose Message Is Highly Expressed in the Testis

Abstract: We cloned cDNA encoding a novel mouse homologue of DNA topoisomerase III (mTOP3␤). The nucleotide sequence contains an open reading frame of 863 amino acids, and the deduced molecular mass of the coded protein is 96.9 kDa. The overall sequence of mTOP3␤ has a 48 and 36% identity with mouse TOP3␣ at the nucleotide and amino acid level, respectively. DNA topoisomerase III␤ was expressed using a baculovirus expression system and purified. The purified DNA topoisomerase III␤ had activity to relax negatively superc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…Thus, it seems likely that one of the possible functions of Sgs1 in the meiotic process is to recruit Top3. In this context, it is interesting that mouse Top3␣ and Top3␤ as well as Blm mRNAs were highly expressed in the testis and that the levels of their expression in the testis were increased simultaneously and markedly by 17 days after birth, when numbers of the cells in pachytene phase increase (39,40,41). In addition, it was reported recently that BLM, one of the Sgs1 homologues in higher eukaryotes, was localized on mouse meiotic chromosomes during meiotic DNA recombination (49).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it seems likely that one of the possible functions of Sgs1 in the meiotic process is to recruit Top3. In this context, it is interesting that mouse Top3␣ and Top3␤ as well as Blm mRNAs were highly expressed in the testis and that the levels of their expression in the testis were increased simultaneously and markedly by 17 days after birth, when numbers of the cells in pachytene phase increase (39,40,41). In addition, it was reported recently that BLM, one of the Sgs1 homologues in higher eukaryotes, was localized on mouse meiotic chromosomes during meiotic DNA recombination (49).…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that top3 + is essential for vegetative growth and faithful chromosome segregation in Schizosaccharomyces pombe (Goodwin et al, 1999;Maftahi et al, 1999). In higher eukaryotic cells, two TOP3 homologues have been found, and designated TOP3 α and β (Hanai et al, 1996;Seki et al, 1998aSeki et al, , 1998b. Knockout of the Top3a gene in mice resulted in embryonic lethality, suggesting that Top3 α is essential for cell viability (Li et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several companies have developed recombinase-based technologies, such as the Invitrogen Gateway cloning technology, Clontech In-Fusion, BioCat Cold-Fusion, and Red/ET Recombination, but these rely heavily on specialized kits containing vectors, enzymes, or hosts (4,7,10,11,14,15 …”
mentioning
confidence: 99%